Visualizing cellular interactions: intravital imaging in tumor microenvironment - Li, Shichao; Liu, Limei; Shan, Juanjuan; Qian, Cheng (Frontiers in Immunology, 2025)
The tumor milieu is a dynamic ecosystem where immune cells, stromal cells, and tumor cells interact to influence tumor progression and anti-tumor immunity. Traditional experimental methods, limited to static in vitro or ex vivo analyses at specific time points, cannot fully capture the complexity and dynamic evolution of the tumor microenvironment (TME) in living organisms. Intravital microscopy (IVM), powered by advanced imaging technologies, precise labeling strategies, and optimized experimental approaches, enables real-time visualization of biological structures and cellular interactions within living animals. This review synthesizes findings from IVM-based research, focusing on the dynamic and transient interactions between tumor cells and other cell types, such as normal epithelial cells, immune cells, and stromal cells. It explores the nature of these interactions, their impact on tumor progression, and the outcomes of therapeutic interventions.Overall, we aim to provide a comprehensive resource that highlights the role of IVM in uncovering the dynamic cellular interplay within the TME and its implications for advancing tumor biological research and improving cancer therapies.